Case Report on Wilson's Disease: An Unusual Presentation (Bangladesh Medical Journal, 2011)
Key Words: Wilson's Disease; Neuropsychiatric disorder; ceruloplasmin; Penicillamine; Zinc acetateDOI: 10.3329/bmj.v39i2.7038Bangladesh Medical Journal 2010, 39(2) pp.50-52